2012
DOI: 10.1007/s12011-012-9534-2
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Modulates Fluoride-Induced Oxidative Hepatotoxicity in Male Wistar Rats

Abstract: The present study is aimed to evaluate the protective effect of ferulic acid (FA) on fluoride-induced oxidative hepatotoxicity in male Wistar rats. Fluoride (25 mg/L) was given orally to induce hepatotoxicity for 12 weeks. Hepatic damage were assessed using status of pathophysiological markers like serum marker enzymes like aspartate transaminase, alanine transaminase, alkaline phosphatase, acid phosphatase, gamma glutamyl transferase, lactate dehydrogenase, bilirubin, lipid profile, total protein content leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Alteration in the activities of hepatic functional marker enzymes such as AST, ALT, and γ‐GT are the direct indication of cellular and functional integrity of hepatic membranes. Our study reveals that fluoride intoxicated rats has increased hepatic marker enzyme activities that are in accordance with previous reports .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Alteration in the activities of hepatic functional marker enzymes such as AST, ALT, and γ‐GT are the direct indication of cellular and functional integrity of hepatic membranes. Our study reveals that fluoride intoxicated rats has increased hepatic marker enzyme activities that are in accordance with previous reports .…”
Section: Discussionsupporting
confidence: 93%
“…This could be one of the reasons for increasing serum fluoride level in fluoride treated rats. Fluoride crosses the cell membrane by simple diffusion and causes liver damage . Alteration in the activities of hepatic functional marker enzymes such as AST, ALT, and γ‐GT are the direct indication of cellular and functional integrity of hepatic membranes.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that ALP was involved in immune defence mechanisms and was correlated with the immune competence (Li et al., ). In studies on rats, the increase in ALP clearly exhibited that FA possessed promising hepato‐protective potential (Krishnan, Prasanna, Sabina, & Rasool, ; Panneerselvam, Subbiah, Arumugam, & Senapathy, ). The improvement of serum biochemistry parameters of FA‐supplemented groups in this study indicated that the tilapia might have better health status.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ROS, LPO, PCC and M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 16 NO are the hallmarks of oxidative insults triggered by various xenobiotics [30][31]. F -is known to induce oxidative stress that has been well demonstrated in several in vitro models [32][33] and in vivo chronic toxicity in experimental animals [34][35] and humans [16]. For the first time we report that acute F -toxicity impairs cardiac function through oxidative myocardial injury.…”
Section: Discussionmentioning
confidence: 99%